Polymer composition

Through the combination of LDPE, HDPE and aliphatic functionalized inorganic nanoparticle fillers, the problem of high conductivity in high-voltage DC cables is solved, and a polymer composition with low DC conductivity and excellent thermomechanical properties is achieved, suitable for high-voltage power cables insulating layer.

CN115038749BActive Publication Date: 2025-01-03BOREALIS AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180012244.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-30
Filing Date
2021-01-29
Publication Date
2025-01-03
Estimated Expiration
2041-01-29

AI Technical Summary

Technical Problem

The existing polymer compositions have high conductivity in high voltage DC cables, resulting in thermal runaway problems and lack alternatives that can meet the low DC conductivity and good mechanical properties that are suitable for demanding power cable applications.

Method used

A mixture of low-density polyethylene (LDPE), high-density polyethylene (HDPE) and aliphatic functionalized inorganic nanoparticle fillers is used to form a polymer composition, which is prepared by specific proportions and processes to form a low DC conductivity and excellent Materials with thermomechanical properties.

Benefits of technology

The low DC conductivity of the polymer composition is achieved, the risk of thermal runaway is reduced, and the thermomechanical properties are maintained or improved, suitable for insulating layer applications of high voltage power cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003776619410000141
    Figure BDA0003776619410000141
  • Figure HDA0003776619420000011
    Figure HDA0003776619420000011
  • Figure HDA0003776619420000021
    Figure HDA0003776619420000021
Patent Text Reader

Abstract

A polymer composition comprising (i) at least 70 wt% of a low density polyethylene (LDPE) homopolymer or copolymer having a molecular weight of 905-935 kg / m 3 (i) 0.5‑20 wt% of a high density polyethylene (HDPE) having a density of 940 kg / m 3 or greater density and an MFR2 of 0.1-50 g / 10 min; and (iii) 0.05-10 wt% of an aliphatic functionalized inorganic nanoparticle filler, preferably an alkyl functionalized inorganic nanoparticle filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polymer composition having advantageously low direct current (DC) conductivity. Specifically, the present invention relates to a polymer composition comprising a mixture of low-density polyethylene (LDPE), high-density polyethylene (HDPE) and aliphatic functionalized inorganic nanoparticle filler, and use of the composition in manufacturing cables, especially in manufacturing power cable insulation layers. Background Art

[0002] Polyolefins produced by high-voltage (HP) processes are widely used in demanding polymer applications, where the polymers must meet high mechanical and / or electrical requirements. For example, in the field of power cable applications, especially in medium voltage (MV) and especially in high voltage (HV) and ultra-high voltage (UHV) cable applications, the electrical properties of the polymer composition are of great importance. Furthermore, the importance of electrical properties may differ in different cable applications, such as in alternating current (AC) and direct current (DC) cable applications.

[0003] A typical power cable comprises a conductor surrounded by at least an inner semiconducting layer, an insulating layer and an outer semiconducting layer. The cable is usually produced by extruding said layers onto the conductor. The polymer material in one or more of said layers is usually cross-linked.

[0004] Electronic conductivity of direct current is an important material property, for example in insulation materials in high voltage direct current (HVDC) cables. First, the strong dependence of this property on temperature and electric field has an impact on the electric field. The second problem is related to the heat generated inside the insulation layer by the leakage current of electricity flowing between the inner and outer semiconducting layers. This leakage current depends on the electric field and the conductivity of the insulation layer. Under high voltage / temperature conditions, the high conductivity of the insulation material may lead to thermal runaway. Therefore, the electronic conductivity must be low enough to avoid thermal runaway.

[0005] Correspondingly, in HVDC cables, the insulation is partially heated by the leakage current. For a particular cable design, the amount of heat generated is proportional to the insulation conductivity × voltage 2. Therefore, if the voltage is increased, more heat will be generated unless the conductivity decreases by a factor higher than the square of the factorial increase in the applied voltage.

[0006] There is a high demand to increase the voltage of direct current (DC) power cables. Therefore, there is a continuous need to find alternative polymer compositions with reduced DC conductivity. Such polymer compositions should also have mechanical properties good enough to meet demanding power cable applications.

[0007] WO2017 / 149086 and WO2017 / 149087 relate to the use of a nanoparticle filler in a polymer composition. However, the use of a mixture of the filler with LDPE and HDPE is not disclosed, and the conductivity of the exemplified composition is still relatively high.

[0008] EP 3261095 relates to a cable comprising a polymer composition comprising a mixture of LDPE and HDPE. However, the use of nanoparticle fillers is not disclosed and the conductivity of the exemplified composition is still relatively high.

[0009] Therefore, there remains a need for a novel polymer composition having a further reduced DC conductivity. The inventors have now demonstrated that a polymer composition comprising a mixture of LDPE, HDPE and aliphatic functionalized inorganic nanoparticle filler has unexpectedly low DC conductivity and is therefore particularly suitable for use in the manufacture of high voltage power cables. It is believed that the claimed combination of components acts as a synergistic combination, providing unexpectedly low DC conductivity. In addition, the polymer composition of the present invention maintains or even improves thermomechanical properties. Summary of the invention

[0010] Therefore, from one aspect, the present invention provides a polymer composition comprising:

[0011] (i) at least 70 wt% of a low density polyethylene (LDPE) homopolymer or copolymer having a molecular weight of 905-935 kg / m 3 density and MFR2 of 0.1-10g / 10min;

[0012] (ii) 0.5-20 wt% of high density polyethylene (HDPE) having a molecular weight of 940 kg / m 3 or greater density and MFR2 of 0.1-50 g / 10min; and

[0013] (iii) 0.05-10 wt% of an aliphatic functionalized inorganic nanoparticle filler, preferably an alkyl functionalized inorganic nanoparticle filler.

[0014] Viewed from a further aspect the invention provides a process for the preparation of a polymer composition as hereinbefore defined comprising mixing:

[0015] (i) at least 70 wt% of a low density polyethylene (LDPE) homopolymer or copolymer having a molecular weight of 905-935 kg / m 3 density and MFR2 of 0.1-10g / 10min;

[0016] (ii) 0.5-20 wt% of high density polyethylene (HDPE) having a molecular weight of 940 kg / m 3 or greater density and MFR2 of 0.1-50 g / 10min; and

[0017] (iii) 0.05-10 wt% of an aliphatic functionalized inorganic nanoparticle filler, preferably an alkyl functionalized inorganic nanoparticle filler.

[0018] From a further aspect, the invention provides a cable comprising a conductor surrounded by one or more layers, wherein one or more of said layers comprises a polymer composition as defined herein before. In a still further aspect, the invention provides a power cable, such as a direct current (DC) power cable, comprising: a conductor surrounded by at least an inner semiconducting layer, an insulating layer and an outer semiconducting layer in sequence, wherein at least one layer, such as at least the insulating layer, comprises a polymer composition as defined herein before.

[0019] Viewed from a still further aspect, the invention provides the use of a polymer composition as herein before defined in the manufacture of a layer in a cable, for example an insulation layer in a power cable. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The conductivity as a function of temperature is shown for the samples disclosed in Table 1. The inventive examples comprising LDPE, HDPE and nanoparticle filler have significantly lower conductivity than the comparative examples comprising only LDPE, LDPE + HDPE or LDPE + nanoparticle filler.

[0021] Figure 2 The storage modulus as a function of temperature is shown for the samples disclosed in Table 1. The inventive examples comprising LDPE, HDPE and nanoparticle filler have significantly improved storage modulus compared to the comparative examples comprising only LDPE, LDPE+HDPE or LDPE+nanoparticle filler. DETAILED DESCRIPTION

[0022] The present invention relates to a polymer composition comprising:

[0023] (i) at least 70 wt% of a low density polyethylene (LDPE) homopolymer or copolymer having a molecular weight of 905-935 kg / m 3 density and MFR2 of 0.1-10g / 10min;

[0024] (ii) 0.5-20 wt% of high density polyethylene (HDPE) having a molecular weight of 940 kg / m 3 or greater density and MFR2 of 0.1-50 g / 10min; and

[0025] (iii) 0.05-10 wt% of an aliphatic functionalized inorganic nanoparticle filler, preferably an alkyl functionalized inorganic nanoparticle filler.

[0026] The amounts of components (i)-(iii) in the composition can vary independently. In one embodiment, the polymer composition comprises: at least 75 wt% of component (i), 0.5-15 wt% of component (ii) and 0.1-10 wt% of component (iii). In one embodiment, the polymer composition comprises: at least 90 wt% of component (i), 1.0-8.0 wt% of component (ii) and 1.0-8.0 wt% of component (iii).

[0027] In one embodiment, the polymer composition consists of components (I)-(iii) such that the total amount of components (I)-(iii) equals 100%. In other embodiments, the polymer composition may include optional further components.

[0028] The present inventors have demonstrated that the polymer compositions described herein have unexpectedly low DC conductivity. In one embodiment, the polymer composition has a DC conductivity of less than 4.0 x 10 -17 S / m; and / or less than 2.5x10 when measured at 60°C -17 S / m; and / or less than 3.5x10 when measured at 90°C -16 S / m. DC conductivity is measured according to the "DC conductivity measurement" described under "Determination method". When measured at 70°C, the lower limit of DC conductivity can be 4.0x10 -19 S / m; and / or less than 2.5x10 when measured at 60°C -19 S / m; and / or less than 3.5x10 when measured at 90°C -19 S / m.

[0029] The polymer composition may be optionally crosslinked. In a preferred embodiment, the polymer composition is not crosslinked. A "non-crosslinked" polymer composition means that the polymer composition in its final form, for example in a layer of a cable, is not crosslinked and is therefore thermoplastic.

[0030] Preferably, the polymer composition has a relative humidity of at least 1.0 x 10 5 The storage modulus (G') of Pa is preferably at least 5.0x10 5 Pa.

[0031] In a preferred embodiment, the polymer composition has a relative humidity of at least 5.0 x 10 4 The storage modulus (G') of Pa is preferably at least 1.0x10 5 Pa.

[0032] In a preferred embodiment, the polymer composition has a relative humidity of at least 3.0 x 10 4 The storage modulus (G') of Pa is preferably at least 5.0x10 4 Typically, the polymer composition measured according to the method described under "Determination Methods" has a relative humidity of up to 1.0 x 10 7 Storage modulus (G') of Pa.

[0033] Component (i) – Low density polyethylene (LDPE)

[0034] According to the present invention, component (i) of the polymer composition is a low density polyethylene (LDPE). According to the present invention, LDPE forms at least 70 wt% of the total polymer composition. In a preferred embodiment, LDPE forms at least 75 wt% of the polymer composition, more preferably at least 90 wt%. The upper limit of LDPE may be 98 wt%.

[0035] Low density polyethylene, LDPE, is a polyethylene produced by a high pressure process. Typically, ethylene and optionally further comonomers are polymerized under high pressure in the presence of an initiator. The meaning of LDPE polymers is well known and documented in the literature.

[0036] Although the term LDPE is an abbreviation for low-density polyethylene, the term is not to be construed as limiting the density range, but covers high-pressure (HP) polyethylenes of low, medium and higher density similar to LDPE. The term LDPE describes and distinguishes high-pressure polyethylene from low-pressure polyethylene produced in the presence of an olefin polymerization catalyst. LDPEs have certain typical characteristics, such as a specifically different branched structure and are essentially free of catalyst residues.

[0037] The LDPE according to the invention may be cross-linked or non-cross-linked. "Non-cross-linked" low density polyethylene (LDPE) means that the LDPE in the layers of the final DC cable (in use) is non-cross-linked and thus thermoplastic.

[0038] The LDPE according to the present invention is a low density homopolymer of ethylene (herein referred to as LDPE homopolymer) or a low density copolymer of ethylene and one or more comonomers (herein referred to as LDPE copolymer). In one embodiment, the LDPE homopolymer or LDPE copolymer is optionally unsaturated. In one embodiment, the one or more comonomers of the LDPE copolymer are selected from the group consisting of polar comonomers, non-polar comonomers or a mixture of polar comonomers and non-polar comonomers.

[0039] In one embodiment, the LDPE is an unsaturated LDPE copolymer of ethylene. In a preferred embodiment, the LDPE is an unsaturated LDPE copolymer of ethylene with at least one polyunsaturated comonomer and optionally one or more other comonomers. In one embodiment, the polyunsaturated comonomer consists of a straight carbon chain having at least 8 carbon atoms and at least 4 carbon atoms between non-conjugated double bonds, at least one of which is a non-conjugated double bond at the end. In a preferred embodiment, the polyunsaturated comonomer is a diene, preferably a diene comprising at least eight carbon atoms, the first carbon-carbon double bond being terminal and the second carbon-carbon double bond being non-conjugated with the first. Preferred dienes are selected from C8-C 14 The non-conjugated diene or a mixture thereof is more preferably selected from 1,7-octadiene, 1,9-decadiene, 1,11-dodecadiene, 1,13-tetradecadiene, 7-methyl-1,6-octadiene, 9-methyl-1,8-decadiene or a mixture thereof. Even more preferably, it is selected from 1,7-octadiene, 1,9-decadiene, 1,11-dodecadiene, 1,13-tetradecadiene or any mixture thereof. In a preferred embodiment, the LDPE is a LDPE homopolymer.

[0040] In one embodiment, the LDPE includes 0.001-35 wt%, such as less than 30 wt%, such as less than 25 wt%, of one or more comonomers relative to the total weight of the entire copolymer. An exemplary range includes 0.5-10 wt%, such as 0.5-5 wt% of comonomer. The comonomer content can be determined using FTIR.

[0041] LDPE has 905-935kg / m 3 In one embodiment, LDPE has a density greater than 905 kg / m 3 Density, for example at least 910 kg / m 3 In one embodiment, the LDPE has a mass of less than 935 kg / m 3 Density, for example 930kg / m 3 In one embodiment, the LDPE has a mass of 910-930 kg / m 3 density.

[0042] LDPE has an MFR2 of 0.1-10 g / 10 min (2.16 kg, 190° C.). In one embodiment, LDPE has an MFR2 greater than 0.1 g / 10 min, such as at least 0.2 g / 10 min. In one embodiment, LDPE has an MFR2 less than 10 g / 10 min, such as 5 g / 10 min or less. In one embodiment, LDPE has an MFR2 of 0.2-5.0 g / 10 min.

[0043] The LDPE of the present invention is not new. Suitable LDPE grades according to the present invention are commercially available.

[0044] Component (ii) - High density polyethylene (HDPE)

[0045] Component (ii) of the polymer composition according to the present invention is high density polyethylene (HDPE). Component (ii) forms 0.5-20 wt% of the entire polymer composition. In one embodiment, component (ii) forms 0.5-15 wt% of the polymer composition, preferably 1.0-8.0 wt%.

[0046] HDPE can be a high density ethylene homopolymer (HDPE homopolymer) or a high density copolymer of ethylene and one or more comonomers (HDPE copolymer). Ethylene copolymer means a polymer in which the majority of the weight is contributed by ethylene monomer units. When the HDPE is a HDPE copolymer, the molar fraction of the comonomer is preferably up to 10%, more preferably up to 5% by mole, for example 0.5-5.0 mol%.

[0047] In one embodiment, the HDPE is a HDPE copolymer of ethylene and one or more comonomers. Other copolymerizable monomers are preferably selected from C3-C 12 , especially C3-C 10 , α-olefin comonomers, especially mono- or poly-olefin unsaturated comonomers, specifically C3-C 10 - α-olefins, such as propylene, but-1-ene, hex-1-ene, oct-1-ene and 4-methyl-pent-1-ene. Particularly preferably, 1-hexene and 1-butene are used.

[0048] In one embodiment, the HDPE is a HDPE homopolymer.

[0049] HDPE can be unimodal or multimodal. A polyethylene composition comprising at least two polyethylene segments is called "multimodal", which have been produced under different polymerization conditions, resulting in different (weight average) molecular weights and molecular weight distributions of the segments. In a preferred embodiment, the HDPE is unimodal.

[0050] HDPE can be made by any conventional process. In one embodiment, a polymerization catalyst is used. Suitable polymerization catalysts include coordination catalysts of transition metals, such as Ziegler-Natta (ZN), metallocenes, non-metallocenes, chromium catalysts, etc. The catalyst can be supported, for example, with conventional carriers containing silicon dioxide, aluminum-containing carriers and magnesium chloride-based carriers. Preferably, the catalyst is a ZN catalyst, and more preferably the catalyst is a silicon dioxide-supported ZN catalyst.

[0051] HDPE has a weight of 940kg / m 3 Preferably, the polymer has a density of 945 kg / m 3 or greater, and more preferably 950 kg / m 3 In one embodiment, the polymer has a mass of 970 kg / m 3 Or lower density, preferably 965kg / m 3 In one embodiment, the HDPE has a mass of 940-970 kg / m 3 The density is preferably 945-965 kg / m 3 .

[0052] HDPE has an MFR2 of 0.1-50 g / 10 min (2.16 kg, 190° C.). In one embodiment, HDPE has an MFR2 of 1.0-20 g / 10 min. In a preferred embodiment, HDPE has an MFR2 of at least 10 g / min, such as 10-20 g / min.

[0053] Suitable HDPE grades according to the present invention are commercially available.

[0054] Component (iii) - Nanoparticle filler

[0055] Component (iii) of the polymer composition according to the present invention is an aliphatic functionalized inorganic nanoparticle filler, preferably an alkyl functionalized inorganic nanoparticle filler. The term "aliphatic functionalized inorganic nanoparticle filler" as used herein refers to an inorganic nanoparticle filler in which the nanoparticles have been modified to bind one or more aliphatic functional groups on the surface of the nanoparticles. Such modifications are well known in the art and are discussed in, for example, WO2006 / 081400. In a preferred embodiment, the aliphatic functional group is an alkyl group, and the nanoparticle filler is an alkyl functionalized inorganic nanoparticle filler.

[0056] The nanoparticles have a diameter of less than 1000 nm, preferably less than 500 nm, more preferably less than 250 nm. The nanoparticles preferably have a diameter of 10 nm or more, for example 25 nm or more. The nanoparticles preferably have a diameter of 10-100 nm, for example 25-75 nm; most preferably a diameter of 40-60 nm. These diameters can be determined by TEM analysis.

[0057] Component (iii) forms 0.05-10 wt% of the entire polymer composition. In a preferred embodiment, the nanoparticle filler forms 0.5-10 wt%, preferably 1.0-8.0 wt% of the polymer composition.

[0058] In one embodiment, the nanoparticle filler comprises nanoparticles selected from inorganic oxides, hydroxides, carbonates, fullerenes, nitrides, carbides, kaolin, talc, borates, alumina, titanium dioxide or titanates, silica, silicates, zirconium oxide, zinc oxide, glass fibers or glass particles, or any mixture thereof. In one embodiment, the nanoparticle filler comprises inorganic oxide nanoparticles, such as alumina, magnesium oxide, zinc oxide, silica, titanium oxide, iron oxide, barium oxide, calcium oxide, strontium oxide nanoparticles or mixtures thereof.

[0059] In one embodiment, the nanoparticle filler comprises MgO, SiO2, TiO2, ZnO, Al2O3, Fe3O4, barium oxide, calcium oxide, strontium oxide nanoparticles or mixtures thereof. Preferably, the nanoparticle filler comprises aluminum oxide, magnesium oxide, zinc oxide nanoparticles or mixtures thereof. Most preferably, the nanoparticle filler comprises aluminum oxide nanoparticles. In a preferred embodiment, the nanoparticle filler comprises Al2O3, MgO, ZnO nanoparticles or mixtures thereof, most preferably Al2O3 nanoparticles.

[0060] The nanoparticles forming the nanoparticle filler according to the present invention are functionalized with aliphatic groups such as alkyl, alkenyl, cycloalkyl, alkylcycloalkyl. In a preferred embodiment, the aliphatic group is an alkyl group so that the nanoparticle filler is an alkyl functionalized inorganic nanoparticle filler. The alkyl group is preferably a C1-20 alkyl group, such as a C4-20 alkyl group, preferably a C6-C20 alkyl group. In a preferred embodiment, the alkyl group is a C6-C12 alkyl group, such as a C8 alkyl group.

[0061] The aliphatic group may be straight chain or branched, preferably straight chain. In a preferred embodiment, the aliphatic group is a straight chain alkyl group, such as a straight chain C1-20 alkyl group, in particular a straight chain C4-20 alkyl group. In a preferred embodiment, the alkyl group is a straight chain C6-12 alkyl group, such as n-octyl.

[0062] The nanoparticles forming the nanoparticle filler can be functionalized by any known method. In one embodiment, the nanoparticle filler can be functionalized by reacting with a kind of aliphatic-functionalized silane, for example alkyl silane. The aliphatic group on such silane is the aliphatic group used for functionalized nanoparticles as described above. In a preferred embodiment, the nanoparticle filler is functionalized by reacting with alkyl (trialkoxy) silane, dialkyl (dialkoxy) silane or trialkyl (alkoxy) silane, preferably alkyl (trialkoxy) silane.

[0063] The alkane portion of the alkoxy group of the silane may be the same as or different from the alkyl group of the silane. 1-10 Alkoxy, especially straight chain C 1-10 Alkoxy groups, such as methoxy or ethoxy groups. For example, in one embodiment, the nanoparticle filler is functionalized by reaction with n-octyl(triethoxy)silane, n-octyl(trimethoxy)silane, di(n-octyl)(diethoxy)silane, or di(n-octyl)(dimethoxy)silane.

[0064] Nanoparticle fillers are typically in the form of solid powders, but may be supported in a vehicle such as a mineral oil, eg, heptane; for example, the mixture of filler and vehicle forms a colloidal dispersion.

[0065] In one embodiment, the aliphatic functionalized inorganic nanoparticle filler has a diameter of less than 1000 nm, preferably less than 500 nm, and particularly less than 250 nm. The aliphatic functionalized inorganic nanoparticle filler preferably has a diameter of 10 nm or greater, such as 25 nm or greater. The aliphatic functionalized inorganic nanoparticle filler preferably has a diameter of 10-100 nm, such as 25-75 nm. Most preferably, it has a diameter of 40-60 nm.

[0066] The reaction between the nanoparticles of the nanoparticle filler and the aliphatic functionalized silane can be carried out in a solution. Suitable solvents are well known to those skilled in the art and include polar and non-polar solvents. In one embodiment, the reaction can be carried out in a solution that includes water, propanol or a mixture thereof. In certain embodiments, a catalyst can be used to promote the hydrolysis and condensation of the silane, such as ammonium hydroxide.

[0067] Optional further components

[0068] In addition, the polymer composition of the present invention may contain, in addition to components (I)-(iii), further components such as polymer components and / or additives, such as additives, for example any antioxidants, scorch retardants (SR), crosslinking promoters, stabilizers, processing aids, flame retardant additives, water tree flame retardant additives, acid or ion scavengers, nanoparticle fillers and voltage stabilizers as known in the polymer field. The polymer composition may include conventionally used additives such as one or more antioxidants and optionally one or more scorch retardants or crosslinking promoters, such as at least one or more antioxidants for wire and cable (W&C) applications. Suitable additives and the amounts of additives are conventional and well known in the art.

[0069] Technology

[0070] In one aspect, the present invention provides a process for preparing a polymer composition, as defined herein, comprising mixing:

[0071] (i) at least 70 wt% of a low density polyethylene (LDPE) homopolymer or copolymer having a molecular weight of 905-935 kg / m 3 density and MFR2 of 0.1-10g / 10min;

[0072] (ii) 0.5-20 wt% of high density polyethylene (HDPE) having a molecular weight of 940 kg / m 3 or greater density and MFR2 of 0.1-50 g / 10min; and

[0073] (iii) 0.05-10 wt% of an aliphatic functionalized inorganic nanoparticle filler, preferably an alkyl functionalized inorganic nanoparticle filler.

[0074] In one embodiment, the process comprises a further step of crosslinking the polymer composition. Crosslinking may be caused by conventional methods known in the art, such as peroxide crosslinking. Preferably, the polymer composition is not crosslinked.

[0075] application

[0076] The polymer composition according to the present invention can be used in any field of application, but is particularly suitable for wire and cable (W&C) applications.

[0077] In one aspect, the present invention provides a cable comprising a polymer composition according to the present invention. The cable according to the present invention comprises a conductor surrounded by one or more layers, wherein one or more of said layers comprises the polymer composition as defined herein. In a further embodiment of the present invention, the cable is a power cable, such as a direct current (DC) power cable, comprising a conductor surrounded in sequence by at least an inner semiconductive layer, an insulating layer and an outer semiconductive layer, wherein at least one of the layers, such as at least the insulating layer, comprises or is composed of the polymer composition as described herein. In one embodiment, the power cable is a high voltage (HV) power cable or an ultra high voltage (UHV) power cable, i.e. a cable capable of operating at voltages higher than 36 kV.

[0078] The invention also provides the use of a polymer composition as described herein in the manufacture of a layer in a cable, such as an insulation layer, preferably a layer in a power cable, such as an insulation layer of a power cable.

[0079] The cable according to the present invention can be prepared by any conventional means. In one embodiment, the cable is prepared by a process comprising the steps of:

[0080] (a) providing and mixing, preferably melt mixing in an extruder, a polymer composition as defined herein,

[0081] (b) (co)extruding the melt mixture of the polymer composition obtained in step (a) onto a conductor to form one or more layers, preferably at least one insulating layer, and

[0082] (c) Optionally, in said at least one layer, preferably in the insulating layer, at least the polymer composition is crosslinked.

[0083] Determination method

[0084] Unless otherwise stated in the descriptive or experimental sections, the following methods were used for property determinations:

[0085] (wt% = weight %)

[0086] density

[0087] The density of the polymer samples was measured according to ISO 1183-2.

[0088] Melt flow rate (MFR)

[0089] Melt flow rate (MFR) is measured according to ISO 1133 and expressed in g / 10 min. MFR is an indicator of polymer fluidity and therefore also of processability. The higher the melt flow rate, the lower the viscosity of the polymer. Unless otherwise stated, the term MFR used herein refers to MFR2 (190°C, 2.16 kg).

[0090] Sample preparation

[0091] The polymer compositions of the invention and the comparative examples were melt compounded in a Micro 5cc twin screw compounder (DSM Xplore) at 150°C for 6 minutes at a screw speed of 100 rpm. The extruded nanocomposite rods were cut into pellets and compression molded into 80 μm thick films at 130°C for 10 minutes using a TP400 laboratory press (Fontijne Grotnes BV, The Netherlands) under a load of 200 kN. The samples were finally cooled to 25°C at a rate of 20°C / min while maintaining the compressive load.

[0092] DC conductivity measurement

[0093] The conductivity measurements were carried out following the standard procedure according to IEC, Test Method for Volume and Surface Resistivity of Solid Electrical Insulating Materials, Standard 60093, 1980, applying a direct current (DC) voltage (Glassman FJ60R2) to the film samples, i.e. the polymer compositions of the present invention and the comparative examples, and measuring the charging current with an electrometer (Keithley 6517A). The current signal was recorded and stored for further analysis by LabVIEW software contained in a personal computer. An oven was used to control the temperature, while an overvoltage protection prevented the electrometer from being damaged by possible overshoots, and a low-pass filter removed high-frequency interference. A stainless steel three-electrode system was used, with the high-voltage electrode being a cylinder of 45 mm diameter, the current measuring electrode having a diameter of 30 mm, and a guard ring eliminating surface currents. Good contact between the high-voltage electrode and the film sample was achieved by placing a layer of Elastosil R570 / 70 (Wacker) between them. The experiments were carried out at 60, 70 and 90°C for 6 hours. The applied voltage was 2.6 kV, corresponding to an electric field of 30 kV / mm, and the given temperature and electric field conditions (60-90°C) simulated the stress conditions in the insulation of real HVDC cables. The test was repeated twice for each material to evaluate the reproducibility.

[0094] Storage modulus (G')

[0095] The storage modulus (G') of the samples was measured by dynamic mechanical thermal analysis (DMTA) as a function of temperature. The storage modulus is expressed in Pa. The polymer melts were characterized by torsional dynamic mechanical thermal analysis (DMTA) using an Anton Paar MCR702 TwinDrive (Graz, Australia) rheometer operated in a single motor-sensor configuration (stress control). The temperature was controlled by a CTD450 convection oven using an SCF cylindrical sample holder. The temperature was increased from 30°C to 130°C at a rate of 2°C / min while the samples were subjected to a strain amplitude of 1% at a frequency of 0.8 Hz. The test specimens were prepared directly from the extruded strands (3 mm diameter) cut to a total length of 40 mm,) resulting in a free sample length of ca. 26 mm, the results are shown in Figure 2 middle.

[0096] Experimental Section

[0097] Material

[0098] The materials used in this work are as follows:

[0099] LDPE: density 922kg / m 3 , MFR21.9g / 10min.

[0100] HDPE: (single-mode Ziegler Natta HDPE, density = 962kg / m 3 , MFR2 = 12g / 10min, 190℃)

[0101] C8-Al2O3: The preparation method is described as follows

[0102] Preparation of Octyl-Coated Alumina Nanoparticles (C8-Al2O3)

[0103] Alumina nanoparticles (NanoDur from Nanophase Inc, CAS No. 1344-28-01, density 3.97 g / cm 3 ) was coated with n-octyltriethoxysilane (Sigma-Aldrich, CAS No. 3069-42-9). The reaction was carried out in a mixed medium of 2-propanol and water. Ammonium hydroxide (aq. 25%) was used as a catalyst to promote the hydrolysis and condensation of silane. After surface modification, the nanoparticles were dried in a vacuum oven (Fisher Scientific Vacucell, MMT Group) at 80°C for 20 hours. According to TEM image analysis, the average diameter of the spherical Al2O3 nanoparticles was 50nm.

[0104] Preparation of polymer compositions

[0105] Octyl-coated alumina nanoparticles (C8-Al2O3) were dispersed in n-heptane (0.3 ml n-heptane / 1 g nanoparticles) and sonicated for 5 minutes, after which 0.02 wt% antioxidant Irganox 1076 (Ciba Speciality Chemicals, CAS No. 2082-79-3) was added. The desired proportions of ground low-density polyethylene LDPE and high-density polyethylene HDPE were added to the nanoparticle suspension. The LDPE / HDPE / C8-Al2O3 slurry was shaken for 1 hour with a Vortex Genie2 shaker (Scientific Instruments Inc) and dried at 80°C overnight. After drying, the powder was shaken for another 30 minutes and then extruded at 150°C and 100 rpm for 6 minutes (Micro 5cc twin-screw compounder, Xploreinstruments). The extruded material was dried in a vacuum oven at 80°C overnight.

[0106] result

[0107] The compositions and properties of the samples of the polymer compositions according to the invention (IE1-3) and the samples of the comparative compositions (CE1-9) are shown in Table 1. The DC conductivity of each sample at each temperature was Figure 1 As shown in the figure.

[0108] Table 1:

[0109]

[0110] The inventors have demonstrated that the compositions of the present invention have excellent low DC conductivity even at high temperatures (e.g., up to 90° C.). Figure 1 From the data in FIG. 1 , it can be seen that the DC conductivity of the compositions IE1-3 of the present invention is unexpectedly more than two orders of magnitude lower than that of the pure LDPE compositions of CE1-3.

[0111] Surprisingly, the conductivity of the inventive examples is also significantly reduced relative to blends consisting of only LDPE and HDPE (CE4-6) or LDPE and nanoparticle filler (CE7-9). The reduction in DC conductivity may even be synergistic.

[0112] Surprisingly, the conductivity of the polymer composition of the present invention is so low, which can be attributed to the different conduction mechanisms of the LDPE / HDPE blend and the LDPE / Al2O3 system. Therefore, it is not expected that the conductivity of the combined polymer composition would be lower than that of the comparative example.

[0113] Further, the polymer compositions of the present invention achieve this reduction in DC conductivity while maintaining or even improving the thermomechanical properties of the polymer composition (for example in terms of storage modulus). This is despite the fact that the presence of nanoparticle fillers may reduce the thermomechanical properties. The introduction of HDPE into LDPE creates a system that is melt miscible and phase separates upon crystallization. This leads to the creation of eutectics, which act as a physically crosslinked network and impart better thermomechanical properties to the system. The introduction of nanoparticles could have disturbed this fine balance, but surprisingly, this was not the case. Analysis of the mixtures showed that the thermomechanical properties of the inventive examples were at least maintained or improved relative to the comparative examples (see Figure 2 ).

[0114] The low electrical conductivity of the compositions according to the invention makes them particularly suitable for use in applications where low electrical conductivity is essential, such as in the insulation of power cables.

Claims

1. A polymer composition comprising: (i) at least 70 wt% of a low density polyethylene homopolymer or copolymer having a molecular weight of 905-935 kg / m2 as measured according to ISO 1183-2 3 A density of 0.1-10 g / 10 min and an MFR2 of 0.1-10 g / 10 min measured at a temperature of 190° C. and a load of 2.16 kg according to ISO 1133; (ii) 0.5-20 wt% of high density polyethylene, having a capacity of 940 kg / m 3 or greater density and MFR2 of 0.1-20 g / 10min; and (iii) 0.05-10 wt% of a C4-C12 alkyl functionalized inorganic nanoparticle filler comprising inorganic oxide nanoparticles, wherein the nanoparticle filler is functionalized by reaction with an alkyl silane.

2. The polymer composition according to claim 1, wherein The nanoparticle filler includes aluminum oxide, magnesium oxide or zinc oxide nanoparticles.

3. The polymer composition according to claim 1, wherein The nanoparticle filler comprises aluminum oxide nanoparticles.

4. The polymer composition according to claim 1, wherein The alkyl group is a straight chain C4-C12 alkyl group.

5. The polymer composition according to claim 1, wherein The alkyl group is a C6-C12 alkyl group.

6. The polymer composition according to claim 1, wherein The alkyl group is n-octyl.

7. The polymer composition according to claim 1, wherein The alkylsilane is an alkyl(trialkoxy)silane or a dialkyl(dialkoxy)silane.

8. The polymer composition according to claim 1, wherein The low density polyethylene is a low density polyethylene homopolymer or an unsaturated low density polyethylene copolymer of ethylene and at least one polyunsaturated comonomer and optionally one or more other comonomers.

9. The polymer composition according to claim 1, wherein The DC conductivity is: When measured at 70°C, less than 4.0x10 -17 S / m; and / or When measured at 60°C, less than 2.5x10 -17 S / m; and / or When measured at 90°C, less than 3.5x10 -16 S / m, The DC conductivity is measured according to the volume resistivity and surface resistivity test method of solid electrical insulating materials, standard 60093, 1980, in accordance with the IEC standard procedure.

10. The polymer composition according to claim 1, wherein The polymer composition is non-crosslinked.

11. The polymer composition of claim 1, comprising: (i) at least 75 wt% low density polyethylene; (ii) 0.5-15 wt% high density polyethylene, and (iii) 0.5-10 wt% of C4-C12 alkyl functionalized inorganic nanoparticle filler.

12. The polymer composition of claim 1, comprising: (i) at least 90 wt% low density polyethylene; (ii) 1.0-8.0 wt% of high density polyethylene, and (iii) 1.0-8.0 wt% of C4-C12 alkyl functionalized inorganic nanoparticle filler.

13. The polymer composition according to claim 1, wherein Its storage modulus is: At 115℃, at least 1.0x10 5 Pa; and / or At 120℃, at least 5.0x10 4 Pa; and / or At 125℃, at least 3.0x10 4 Pa; Wherein, the storage modulus is measured by dynamic mechanical thermal analysis.

14. A process for preparing a polymer composition according to any one of claims 1 to 13, comprising mixing: (i) at least 70 wt% of a low density polyethylene homopolymer or copolymer having a molecular weight of 905-935 kg / m 3 density and MFR2 of 0.1-10g / 10min; (ii) 0.5-20 wt% of high density polyethylene, having a capacity of 940 kg / m 3 or greater density and an MFR2 of 0.1-20 g / 10min; and (iii) 0.05-10 wt% of a C4-C12 alkyl functionalized inorganic nanoparticle filler comprising inorganic oxide nanoparticles, wherein the nanoparticle filler is functionalized by reaction with an alkyl silane.

15. A cable comprising a conductor wrapped by a single or multiple layers, wherein: The single or multiple layers comprise the polymer composition according to any one of claims 1-13.

16. A power cable comprising a conductor which is at least sequentially wrapped by an inner semiconductive layer, an insulating layer and an outer semiconductive layer, wherein: At least one layer comprises the polymer composition according to any one of claims 1-13.

17. A power cable as claimed in claim 16, wherein: The power cable is a high-voltage power cable or an ultra-high-voltage power cable.

18. Use of a polymer composition as claimed in any one of claims 1 to 13 in the manufacture of a layer in a cable.